OPTIMIZATION OF Agrobacterium-MEDIATED GENETIC TRANSFORMATION OF oshox4 GENE IN SATOIMO TARO (Colocasia esculenta var. antiquorum) - N. Sri Hartati (BRIN - Badan Riset dan Inovasi Nasional, 2022)
Satoimo (Colocasia esculenta var. antiquorum) can be considered as an alternative food to support food diversification. The aim of this research was to obtain an optimum condition of the genetic transformation method of Satoimo taro through Agrobacterium-mediated genetic transformation using binary vector harboring gene construct of oshox4 and hpt gene as a selectable marker to produce transgenic plants. Plant materials that were used in this study were meristem, root, leaf, petiole, and basal stem. Transformation procedures were carried out using three different co-cultivation periods (1, 2, and 3 days) and different optical densities of A. tumefaciens cells (0,5 and 0,7). Furthermore, callus induction was performed on MS medium containing 2.4-D, cefotaxime, hygromycin and then regenerated on MS medium containing thidiazuron and hygromycin. The putative transgenic plantlets were selected on MS medium containing hygromycin and analyzed using PCR. The results showed that putative transgenic plants derived from the basal stem could survive on a selection medium containing hygromycin and based on PCR analysis some of them contained the oshox4 and hpt genes.